2007
DOI: 10.1073/pnas.0610208104
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic identification of targets of the Arabidopsis sucrose nonfermenting-like kinase SnRK2.8 reveals a connection to metabolic processes

Abstract: SnRK2.8 is a member of the sucrose nonfermenting-related kinase family that is down-regulated when plants are deprived of nutrients and growth is reduced. When this kinase is over expressed in Arabidopsis, the plants grow larger. To understand how this kinase modulates growth, we identified some of the proteins that are phosphorylated by this kinase. A new phosphoproteomic method was used in which total protein from plants overexpressing the kinase was compared with total protein from plants in which the kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 66 publications
5
105
1
Order By: Relevance
“…Similarly to SnRK2.2, SnRK2.3, and SnRK2.6, this enzyme is involved in the control of stress-responsive gene expression. It has also been shown that SnRK2.8 is a positive * This work was supported by Ministry of Science and Higher Education regulator of plant growth, most probably by phosphorylation and regulation of the activity of several enzymes involved in metabolism (13). The results of Diédhiou et al (14) have revealed that overexpression of SAPK4 (a rice SnRK2) increases rice tolerance to salinity and oxidative stress.…”
mentioning
confidence: 76%
“…Similarly to SnRK2.2, SnRK2.3, and SnRK2.6, this enzyme is involved in the control of stress-responsive gene expression. It has also been shown that SnRK2.8 is a positive * This work was supported by Ministry of Science and Higher Education regulator of plant growth, most probably by phosphorylation and regulation of the activity of several enzymes involved in metabolism (13). The results of Diédhiou et al (14) have revealed that overexpression of SAPK4 (a rice SnRK2) increases rice tolerance to salinity and oxidative stress.…”
mentioning
confidence: 76%
“…The identification of SnRK2.5 suggests a link to further cytosolic signaling cascades. Members of the SnRK family were previously associated with signaling in relation to metabolic stresses (98,99), and in particular the SnRK2 kinases were suggested to function in intracellular osmotic responses (26). There are indications that phosphorylation is required for the activation of SnRK2.5, but the precise sites of activation are not yet identified (25).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments isolating compartments of the endomembrane system were performed successfully using either ICAT (Dunkley et al, 2004) or iTRAQ (Dunkley et al, 2006). Similarly, studies investigating changes in protein phosphorylation under various treatment conditions or developmental stages in plants have been performed using 2-D gels (Shin et al, 2007), in vivo metabolic labeling (Benschop et al, 2007), iTRAQ (Nü hse et al, 2007), and label-free methods (Niittyla et al, 2007). Therefore, multiple methods are capable of providing important new insights into plant biology.…”
Section: Considerations For Initiating Quantitative Proteomic Experimmentioning
confidence: 99%